A Geospatial Analysis of Air Traffic Destinations. - Murry, Katrina (My University, 2009)
Studies of air traffic flows in the United States have generally focused on hubs. When origin/destination traffic is analyzed at the nal destination level a more nuance picture emerges. This study looks at the final destination cities for flights originating in Portland, OR (PDX), Lansing, MI (LAN), and Madison, WI (MSN). The flows were initially modeled using a simple gravity model based on the destination, population and distance/cost.
Color poster with text, maps, and graphs (Spring 2009)
Keywords: Air travel--United States--Models; Origin and destination traffic surveys--United States; Posters